Themes of law and rights in Abay Kunanbaev’s work - Shurentayev, А.; Kushkinbayeva, Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The article is a scientific analysis of the works of the great thinker A.Kunanbayev in the context of aspects of law and legality. It is stated that his work includes poems, epics, songs and translations that reflect the most pressing issues of public and political life of the Kazakh people. The article is dedicated to the fact that A.Kunanbayev focuses primarily on the problem of human rights protection in his works. The author of the article compares the Kazakh law «Erezhe», created by Tole Bi (judge) and which became a significant event in the life of the Kazakh people, and Abai’s «words of edification», finding significant points of contact, arguing that the strict principles of «Erezhe» are presented in the «words of edification» as key issues. The article defines that a clear definition of the concept of «law» is contained in the words of Abay: «The law is a set of rules and regulations that lead to justice, peace and tranquility». The article also substantiates the need for further active study of the Kazakh thinker’s works from a legal perspective in connection with the discovery of new Abai’s texts